Gastrodiplomacy in Representing Local Culinary Identity: A Case Study of Senja Eatery in Labuan Bajo - Yulianus Janur; Yohana Etheldreda Ine Dae; Andriano Calrinto Mami; I Wayan Duartha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines how Senja Eatery, a culinary business in Labuan Bajo, West Manggarai, implements gastrodiplomacy as a cultural diplomacy strategy to represent local culinary identity. Using a qualitative approach with participatory observation, semi-structured interviews, and documentation, the research reveals three main findings. First, Senja Eatery successfully builds a strong experiential branding through an instagramable semi-outdoor concept that leverages the natural sunset moment. Second, the kitchen team acts as cultural actors who maintain the authenticity of local ingredients and traditional cooking techniques (marination, smoking for Se'i menu) while negotiating taste adaptations for international tourists. Third, the menu Nasi Campur Manggarai, Lomak, Sayur Watulangkas, Lumpia Melo, and Sopihito explicitly embeds local geographical names and social values, functioning as a medium for cultural promotion. However, a gap exists in written storytelling: the menu book remains standard and has not optimally leveraged the gastronomy narrative potential. This study contributes theoretically to micro-level gastrodiplomacy literature involving non-state actors in tourism destinations.